IMPROVEMENT OF MARKETING RESEARCH IN OIL PRODUCTION ENTERPRISES (European Journal of Interdisciplinary Research and Development, 2022)
In this article, the theoretical and methodological foundations of marketing research in oil production enterprises are studied, and the author comments on the regional analysis and segmentation of the market. The author presented scientific proposals and recommendations on the development of a marketing strategy for the formation of marketing research in oil production enterprises.